Patient decision-making and clinical outcomes following endoscopic therapy or esophagectomy for Barrett’s neoplasia - Robert Lockwood; Elissa Ozanne; Chin Hur; Patrick Yachimski (Endoscopy International Open, 2017)
Background and study aims The objective of this study was to assess patient involvement in decision-making, decision confidence, and decision regret among patients who had undergone endoscopic eradication therapy (EET) or esophagectomy for Barrett’s esophagus (BE) associated neoplasia. Patients and methods Patients with BE high grade dysplasia or intramucosal (T1a) adenocarcinoma who had undergone EET or esophagectomy were invited to complete a survey. Results The cohort included 50 subjects, 70 % (35/50) of whom had undergone EET and 30 % (15/50) of whom had undergone esophagectomy. Subjects who underwent esophagectomy were more likely to report post-treatment dysphagia (47 % vs 14 %, P = 0.03), post-treatment dietary modification (73 % vs 6 %, P < 0.0001), and were less likely to view their post-treatment health favorably. However, when asked whether they had selected the right treatment, a high degree of confidence was reported by both groups (mean 9.8 for EET vs 9.3 for esophagectomy on a 0 – 10 scale, P = 0.12). In fact, 97 % (34/35) of EET patients and 80 % (12/15) of esophagectomy patients indicated they would select the same treatment option (P = 0.08). Conclusions Patients who have undergone EET or surgery for BE neoplasia report a high degree of involvement in the decision-making process. Although EET patients report fewer symptom-specific outcomes, measures of decision confidence and decision regret do not differ between the two treatment groups.